Croatia seeks new spirit of enterprise. Issue 5 (8th April 2014) - Unknown
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to review the latest management developments across the globe and pinpoint practical implications from cutting-edge research and case studies. Design/methodology/approach – This briefing is prepared by an independent writer who adds his own impartial comments and places the articles in context. Findings – Croatian manufacturing industry is strong on ideas but less impressive when it comes to actually generating radical product innovation. The authors make recommendations for improving the current state of affairs. Practical implications – The paper provides strategic insights and practical thinking that have influenced some of the world's leading organizations. Originality/value – The briefing saves busy executives and researchers hours of reading time by selecting only the very best, most pertinent information and presenting it in a condensed and easy-to-digest format.